The meaning of disgust - McGinn, Colin, 1950- (New York ; Oxford : Oxford University Press, 2011)
'The Meaning of Disgust' is an original study of a fascinating but neglected subject, which attempts to tell the disturbing truth about the human condition.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Aversion